1959
DOI: 10.1139/v59-250
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Ketone and Tertiary Amine Groups

Abstract: I7apor pressure studies of trimethylamine and ketones in heptane solution have shown that unstable complexes are formed with cyclohesano~~e a t 0' and with cyclohexanone artd cyclope~~tanone a t -40'. No complex formation was observed with methylethyl ketone, diethyl ketone, or cyclopentar~one a t 0'.Robinson and co-workers (1, 2) originally suggested that there was some type of interaction between a lceto group and a tertiary arnine group in certain allcaloids having these groups in a large-membered ring, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1963
1963
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…It has been previously reported that esters can act as electron acceptors with amines as electron donors to form ion pairs when irradiated in the presence of each other. Interactions between tertiary amines and carbonyl compounds in the ground state can lead to formation of unstable complexes . It is noted that similar interactions cannot be excluded in the present case.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…It has been previously reported that esters can act as electron acceptors with amines as electron donors to form ion pairs when irradiated in the presence of each other. Interactions between tertiary amines and carbonyl compounds in the ground state can lead to formation of unstable complexes . It is noted that similar interactions cannot be excluded in the present case.…”
Section: Resultsmentioning
confidence: 68%
“…Interactions between tertiary amines and carbonyl compounds in the ground state can lead to formation of unstable complexes. 46 It is noted that similar interactions cannot be excluded in the present case. It is also possible that excitation of the CuBr 2 /Me 6 TREN complex can result in reduction with subsequent activation of alkyl bromide.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…S4 †) and/or from complexes of carbonyl compounds with PMDETA. 25 To further understand which component of the catalytic system was responsible for the reduction of GO, the effect of individual components was investigated. A control experiment of GO in anisole without any other compound did not lead to any change in electrical conductivity (see Table 1, entry 9).…”
Section: Entrymentioning
confidence: 99%
“…However replacement of all three hydrogen atoms in ammonia by methyl groups causes significant differences in behaviour from that of the primary or secondary amine. (1) , by Halban (13) and by Wheeler and Levy (14). Wolff and Würtz (5) have investigated the IL/,/7-dime thy Ime than amine and hexane system at 223 Κ to 293 Κ over the whole of the concentration range.…”
Section: /1/-dimethylmethanaminementioning
confidence: 99%